1995
DOI: 10.1111/j.1365-2958.1995.mmi_17020357.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a chemotaxis operon with two cheY genes in Rhodobacter sphaeroides

Abstract: A large chemotaxis operon was identified in Rhodobacter sphaeroides WS8-N using a probe based on the 3' terminal portion of the Rhizobium meliloti cheA gene. Two genes homologous to the enteric cheY were identified in an operon also containing cheA, cheW, and cheR homologues. The deduced protein sequences of che gene products were aligned with those from Escherichia coli and shown to be highly conserved. A mutant with an interrupted copy of cheA showed normal patterns of swimming, unlike the equivalent mutants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
73
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(75 citation statements)
references
References 26 publications
2
73
0
Order By: Relevance
“…Deletion of cheW produces enhanced responses, under aerobic and anaerobic conditions, to the addition and removal of sugars such as mannitol and fructose. This behaviour is also seen in R. sphaeroides cheA mutant tethered cells which showed an enhanced response to fructose even though responses to all other chemoeffectors remained apparently normal (Ward et al, 1995a). These data suggest that cheW and cheA may form a signal-transduction pathway involved in controlling the strength and type of response to sugars such as mannitol and fructose.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…Deletion of cheW produces enhanced responses, under aerobic and anaerobic conditions, to the addition and removal of sugars such as mannitol and fructose. This behaviour is also seen in R. sphaeroides cheA mutant tethered cells which showed an enhanced response to fructose even though responses to all other chemoeffectors remained apparently normal (Ward et al, 1995a). These data suggest that cheW and cheA may form a signal-transduction pathway involved in controlling the strength and type of response to sugars such as mannitol and fructose.…”
Section: Discussionmentioning
confidence: 53%
“…Previous studies suggested that the expression of the R. sphaeroides cheW gene may interfere with the chemosensory signal-transduction pathway of E. coli (Ward et al, 1995a). To analyse this further, the R. sphaeroides cheW gene was cloned into the IPTG-inducible E. coli expression vector pTM30 such that cheW was under the control of the ptac promoter.…”
Section: Expression Of R Sphaeroides Chew In E Coli Chemotaxis Strainsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, R. centenum has two CheY homologs, one fused to CheA and the other free existing. More than one CheY homolog has been reported to exist in the photosynthetic bacterium Rhodobacter sphaeroides (44) as well as in Rhizobium meliloti (13). A dendograph of the various CheY proteins indicates that the R. sphaeroides and R. meliloti CheY1 proteins form a separate lineage from the CheY2 proteins of these species (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A chemotaxis operon has been identified in R. sphaeroides containing homologues of the enteric cheA, chew, cheR and two cheY genes, but lacking cheB and cheZ homologues (Ward et al, 1995a). In contrast to the enterics, mutation of these chemotaxis genes in R. sphaeroides has little effect on chemotaxis to most chemoattractants (Hamblin et al, 1997).…”
Section: Introductionmentioning
confidence: 99%